Age-structured human capital and spatial total factor productivity dynamics - Tapas Mishra; Adusei Jumah; Mamata Parhi (Institute for Advanced Studies (IHS), 2008)
This paper models total factor productivity (TFP) in space and proposes an empirical model for TFP interdependence across spatial locations. The interdependence is assumed to occur due to age-structured human capital dynamics. A semi-parametric spatial vector autoregressive framework is suggested for modeling spatial TFP dynamics where the role of demographic state and technological change are explicitly incorporated in the model to influence their spatial TFP co-movements. Empirical scrutiny in case of Asian countries suggests that cross-country human capital differences in their accumulation and appropriation pattern significantly influenced TFP volatility interdependence. The finding of complementarity in TFP in spatial locations calls for joint policy program for improving aggregate and individual country welfare.
Keywords: C14; C31; E61; N10; O30; O47; 330; total factor productivity; spatial growth; non-linearity; human capital; age-structure; semiparametric VAR; Produktivität; Wirtschaftswachstum; Humankapital; Altersstruktur der Bevölkerung; Nichtlineares Verfahren; VAR-Modell; Asien